Facing the Mobile Revolution: A Romanian Insight - Victoria Stanciu; Mirela Gheorghe (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research question: Are the accounting graduates prepared to deal with mobile devices' security issues? Motivation: Nowadays, mobile computing is a part of the younger generation, the entering workforce in coming years, and from this point of view the BYOD (Bring Your Own Device) approach will continue its increasing trend. The authors investigated the accounting bachelors' knowledge in regard with mobile devices' use aiming at signaling the existing gap on mobile devices' security awareness. IT security specialists consider that both, academia and industry should focus their security awareness campaigns aiming at combat the false sense of security that mobile devices' users have. Idea: The authors aimed at providing an in-depth understanding of the accounting students' profile as mobile devices' users and their knowledge and awareness in regard with mobile security threats. Data: The analyzed sample includes 180 subjects, out of which 81% are bachelors in accounting (38% 1st year; 43% 3rd year) and 19% master students in accounting and banking. Tools: The literature review helped us in structuring our research objectives and design a multiple-choice questionnaire used in the empirical study. Findings: The study reflects the students' insufficient information in regard with mobile devices features and security issues. This is the result of the limited IT lectures and seminars in the curriculum and the insufficient focus on mobile devices' use in the accounting profession. Students should understand the mobile devices as complex devices providing diverse features, not limited to communication with friends and Internet information searching. Contribution: The study contributes towards closing the existing gap in the Romanian research and literature in regard with young generation insufficient knowledge on mobile devices' security and the potential threat brought by BYOD on the companies' IT environment.
Keywords: A2; I25; M15; 650; Mobile devices; threat; mobile security; BYOD